Multi-scale ensemble properties of the Escherichia coli RNA degradosome - Dendooven, Tom (Mol Microbiol, 2022)
In organisms from all domains of life, multi-enzyme assemblies play central roles in defining transcript lifetimes and facilitating RNA-mediated regulation of gene expression. An assembly dedicated to such roles, known as the RNA degradosome, is found amongst bacteria from highly diverse lineages. About a fifth of the assembly mass of the degradosome of Escherichia coli and related species is predicted to be intrinsically disordered – a property that has been sustained for over a billion years of bacterial molecular history and stands in marked contrast to the high degree of sequence variation of that same region. Here, we characterize the conformational dynamics of the degradosome using a hybrid structural biology approach that combines solution scattering with ad hoc ensemble modelling, cryo-electron microscopy, and other biophysical methods. The E. coli degradosome can form punctate bodies in vivo that may facilitate its functional activities, and based on our results, we propose an electrostatic switch model to account for the propensity of the degradosome to undergo programmable puncta formation.